Leveraging IPFS for Secure, Distributed Blockchain Data Infrastructure and Enhanced Security - Sandy Setiawan; Muchlisina Madani; Sondang Visiana S; Elisa Ananda Natalia; Khairunnisa, Novita; Kristina Vaher (Blockchain Frontier Technology, 2025)
In an increasingly digital world, where centralized storage systems dominate and censorship risks are growing, the InterPlanetary File System (IPFS) has emerged as a promising decentralized data storage solution. This research aims to evaluate the potential and challenges of implementing IPFS, using a descriptive qualitative approach that includes both a comprehensive literature review and technical simulations. The literature review highlights IPFS’s advantages, particularly in areas such as data integrity, resistance to censorship, and efficient content distribution. However, it also identifies key challenges, such as high latency and the dependency on node availability. To further investigate these issues, technical simulations were conducted using a private IPFS network, testing file access latency under different network conditions. The results indicate that the fastest average latency occurs when all nodes are active, at 150 ms, while the highest latency is observed when files are accessed through a public gateway, with an average of 540 ms. These findings demonstrate that IPFS has substantial potential to create a more open, decentralized digital ecosystem that resists centralized control. However, for large-scale adoption to be feasible, significant improvements in infrastructure, particularly node availability and latency management, are required to fully support IPFS’s widespread implementation.